Policing the Seas: Building Constabulary Maritime Governance in the Horn of Africa – The Case of Djibouti and Kenya. Issue 3 (2nd October 2019) - McCabe, Robert
ABSTRACT: The upsurge of Somali based maritime piracy after 2005 resulted in considerable international activity in the Horn of Africa, ranging from naval missions to capacity building projects. It also ushered in a new focus by regional states on the dangers as well as the opportunities associated with the sea. In Kenya and Djibouti, two states directly impacted by piracy, this resulted in a strategic shift toward the ocean, breaking with a historical land-centric security approach, in an attempt to reform their domestic maritime sectors and coastal governance architectures by capitalizing on assistance from external capacity building providers. This article adds rigor to the field of maritime security studies by zooming in on how two key littoral states have reformed their domestic maritime sectors following a decline in acts of piracy. It explores important questions such as how have Djibouti and Kenya approached maritime governance historically? How are their territorial maritime spaces delineated and defined? How has the phenomena of piracy influenced the development of coastal governance in both countries? Has this led to innovative practices? Can these practices be applied in other jurisdictions? Finally, what has been the impact of external capacity building assistance on the development of both Djibouti and Kenya's maritime sector and respective approaches to coastal governance and enforcement? This research is significant as it sheds new light on the limitations and challenges facing domestic maritime security sectors in Africa, but also highlights new ways states can improve and build maritime constabulary governance through international partnerships, capacity development and embracing the blue economic agenda using the cases of Djibouti and Kenya as archetypal models.